2020
DOI: 10.1103/physrevresearch.2.043038
|View full text |Cite|
|
Sign up to set email alerts
|

Synchronizing an oscillatory medium: The speed of pacemaker-generated waves

Abstract: In an oscillatory medium, a region which oscillates faster than its surroundings can act as a source of outgoing waves. Such pacemaker-generated waves can synchronize the whole medium and are present in many physical and biological systems, where they are a means of transmitting information. Through numerical simulations, we quantify how the properties of the pacemaker and the underlying limit cycle determine the wave speed, as well as the speed with which they overtake the medium. We compare oscillators based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…1a). In our previous paper we showed that the envelope does not need to spread linearly [1]. This can happen when ε is large, or when the size of the pacemaker or its frequency difference with the outside medium is too small.…”
Section: Setupmentioning
confidence: 98%
See 3 more Smart Citations
“…1a). In our previous paper we showed that the envelope does not need to spread linearly [1]. This can happen when ε is large, or when the size of the pacemaker or its frequency difference with the outside medium is too small.…”
Section: Setupmentioning
confidence: 98%
“…A numerical study of the influence of the diffusion constants can be found in Ref. [1]. To modify the characteristics of the underlying oscillator, we focus on a single parameter: ε, which determines the timescale separation.…”
Section: Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…It would be interesting to see how different types of oscillators (i.e. sinusoidal vs. relaxation oscillators) affect the wave properties, which has recently been characterized in the context of pacemaker-driven waves in reaction-diffusion systems [38]. The type of coupling used in the model offers another possibility to study in more detail.…”
Section: B Future Workmentioning
confidence: 99%